Stress at workplace among teachers in Paka / Norlisa Mat Nor - Mat Nor, Norlisa (2020)
The study aimed to find out and to measure the factors that influence teachers’ stress at workplace in Paka area. Based on literature review, five factors which is role conflict, relationship with others, workload pressure, homework interface and performance pressure were chosen. From this factors, the researcher will measure level of job stress among teachers in Paka schools. In term of research design, methodology and approach, the researcher will use questionnaire whereby a total of 256 teachers from 5 selected school in Paka were given a set of questionnaire through Google Form. The study was used the Descriptive Research Design to examine the relationship between two variables; Dependent Variable (Job Stress) and Independent Variables (Role Conflict, Relationship with Others, Workload Pressure, Homework Interface and Performance Pressure). The researcher using SPSS software to analyse the results to determine which aspect of the factors were most influenced to teachers’ stress at workplace in Paka area. The finding from this research gave valuable insight about a level of stress among teachers and it will help responsible party to determine the best way to ensure this matter can be reduce. The result show that role conflict is the most factor that influenced teachers’ stress at workplace in Paka area. Based on finding, it can be conclude that most of respondent are in the moderate level of stress at workplace and this problem still under control and not really serious.